2019
DOI: 10.1111/scs.12794
|View full text |Cite
|
Sign up to set email alerts
|

No time for reflection: Patient experiences with treatment‐related decision‐making in advanced prostate cancer

Abstract: No time for reflection: Patient experiences with treatment-related decision-making in advanced prostate cancer Background: The rationale of the study was the predominant understanding that patient involvement in treatment-related decision-making is essential and that communication with cancer patients can affect their quality of life, satisfaction with care, and psychosocial and medical outcomes positively. Aim: This study explored how patients with advanced prostate cancer experience the communication with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In this study, we found that patients were often given lots of information immediately after they had received bad news. However, this and other studies have found that patients' attention to and recall of information provided during bad news consultations is poor; and the emotional toll of bad news, increased levels of distress or anxiety, might be responsible for this hampered information processing (Maharaj et al, 2018;Netsey-Afedo et al, 2019;Speer et al, 2017;Tarrant et al, 2008;van Osch et al, 2014). Participants in this study found it helpful when professionals provided emotionally responsive communication, emotional support or opportunities to go back to them for clarification and further information.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In this study, we found that patients were often given lots of information immediately after they had received bad news. However, this and other studies have found that patients' attention to and recall of information provided during bad news consultations is poor; and the emotional toll of bad news, increased levels of distress or anxiety, might be responsible for this hampered information processing (Maharaj et al, 2018;Netsey-Afedo et al, 2019;Speer et al, 2017;Tarrant et al, 2008;van Osch et al, 2014). Participants in this study found it helpful when professionals provided emotionally responsive communication, emotional support or opportunities to go back to them for clarification and further information.…”
Section: Discussionmentioning
confidence: 56%
“…There has been a growing body of qualitative research examining men's experience of and need for supportive care (Arrington, 2015;Bamidele et al, 2018;Chambers et al, 2018;Dunn et al, 2020;King et al, 2015;Kirkman et al, 2017;Netsey-Afedo et al, 2019;Paterson et al, 2015;Paterson et al, 2017;Schildmeijer et al, 2019). These studies helped to identify priority areas of unmet informational need, such as diagnostic tests (e.g., PSA), treatment options and outcomes, prognosis and adverse effects of treatment (short term and long term) and their management (Bamidele et al, 2018;Chambers et al, 2018;Dunn et al, 2020;King et al, 2015;Netsey-Afedo et al, 2019;Paterson et al, 2015;Paterson et al, 2017;Schildmeijer et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, several interviewees felt overlooked and ignored, as well as uninformed. Numerous studies report similar findings where patients and families experienced lack of information, respect and empathy during hospitalisation, which made them feel vulnerable and emotionally distressed (43, 47, 48). Being admitted to a caring ward and feeling well informed have been found to lead to higher patient satisfaction and even improved survival (42, 49).…”
Section: Discussionmentioning
confidence: 91%
“…[24][25][26][27][28][29][30] Shared decision making is relevant because these therapies have not been compared directly, and they have different toxicity profiles. [31][32][33][34][35] Patients must weigh potential benefits and harms against personal priorities. In addition, men with mCRPC report a poor understanding of treatments, [36][37][38][39] which is exacerbated by cognitive dysfunction related to androgen-deprivation therapy.…”
Section: Introductionmentioning
confidence: 99%